The Role of Pre-Pandemic Mental Health Status and Personality Traits on Psychological Distress during the COVID-19 Lockdown among Italian Young Adults - Daniela Marchetti; Lilybeth Fontanesi; Elena Camisasca; Marco Colasanti; Venusia Covelli; Serena Di Giandomenico; Sarah Miragoli; Maria Cristina Verrocchio (Behavioral Sciences, 2023)
The COVID-19 pandemic imposed changes on day-to-day activities and had a detrimental psychological effect on the population, especially among vulnerable individuals, such as adolescents and young adults. The current study aimed to explore variables associated with anxiety, depressive and somatic symptoms in a sample of 608 Italian young adults aged 18 to 25. Data were collected using an online questionnaire administered two months into the COVID-19 lockdown, which explored several areas including sociodemographic information, pre-pandemic and current psychological distress, pre-pandemic and current levels of loneliness, and the traits of intolerance of uncertainty and boredom susceptibility. Results highlighted that having pre-existing mental health issues, being female, and the personality traits of intolerance to uncertainty and boredom susceptibility all played a role in the psychological distress experienced during the pandemic. COVID-19 contributed to negative impacts on young adults’ mental health, highlighting the necessity to develop protective psychological intervention tailored for this vulnerable population.